Geneva® Series Rootstocks for Apple Trees Under Extreme Replanting Conditions in Southern Brazil - Rufato, Leo; da Silva, Pricila Santos; Kretzschmar, Aike Anneliese; Bogo, Amauri; de Macedo, Tiago Afonso; Welter, Juliana Fátima; Fazio, Gennaro; Petry, Daiana (Frontiers in Plant Science, 2021)
The Geneva® rootstocks in Brazil are known to be efficient in controlling vigor, are precocious and resistant to diseases. The objective of this study was to evaluate the performance of apple tree cultivars grafted on the Geneva® rootstocks in severe replant disease areas, by planting 60 days after the eradication. The experiments were implemented in 2017, in São Joaquim and Vacaria. The cultivars Gala Select and Fuji Suprema grafted onto rootstocks ‘G.202’, ‘G.814’, ‘G.210’ and ‘G.213’ in Tall Spindle training system. In 2018/2019 total thinning was carried out to promote plant growth. In the São Joaquim, partial thinning was carried out in 2019/2020 harvest of the ‘Gala Select’. For both areas and cultivars, rootstocks were divided into two groups as to vigor, ‘G.202’ and ‘G.213’ were 40% less vigorous than ‘G.210’ and ‘G.814’. For ‘Gala Select’, the extreme non-fallow condition mainly affected the vigor and productivity of ‘G.213’ in both areas. At the end of two harvests the ‘G.213’ was 17% less productive than ‘G.210’, contrary to what is observed in areas where the fallow period is respected. However, ‘G.213’ confirmed its condition of greater yield efficiency, 27% higher than ‘G.210’. This suggests a perspective of forecasting production for the third crop higher for ‘G.213’ than for ‘G.210’. For ‘Fuji Suprema’, ‘G.210’ rootstock was the most productive in both areas. In São Joaquim, ‘G.202’ matched ‘G.210’ in productivity and efficiency as it sprouts better in colder regions. As the fruit quality, ‘G.213’ anticipated the maturation with fruits of larger size and higher TSS in both areas and cultivars, making possible to anticipate the harvest. It was concluded that the non-fallow condition does not alter the relative differences in vigor and fruit quality among the rootstocks. However, notwithstanding the overall replant tolerance of these rootstocks it does reduce productivity by mainly affecting less vigorous rootstocks that need about three crops to overcome the allelopathic effect of the soil and start growing normally. The G.210 semi-dwarfing rootstock is an alternative for the immediate conversion of apple orchards of Gala Select and Fuji Suprema cultivars, in southern Brazil.